Pengaruh Gelombang Mikro terhadap Kualitas Hasil Minyak Atsiri Jahe (Zingiber officinale) dengan Hidrodistilasi - Bambang Dwi Argo; Febriyanti Ariska Amaliyah (agriTECH, 2020)
Essential oil commodity is one form of strategic export product that has high economic value, one of which is ginger essential oil.  The optimal method of extraction ginger essential oil is still a research topic in an effort to increase its quantity and quality. The purpose of this research is to obtain the optimal heating process parameters with microwave. Ginger essential oil produced by hydro-distillation and microwave pretreatment with 100 and 180 W of maximum output and 1, 2, 3, 4, and 5 min of pretreatment duration. Parameters of essential oil obtained were evaluated, i.e. yield, density, refractive index; total acid number, and zingiberene content. The results indicated that microwave pretreatment with 100 W and 2 min as the best microwave pretreatment combination. The combination produced ginger essential oil with 1.364% of yield, 0.889 g/mL of density, 1.49 of refraction index, 1,5 of total acid number, and 24.7% of zingiberene content. The parameters of the microwave heating process as pretreatment have succeeded in producing ginger essential oil with better quantity and quality.